Examining women journalists in Surabaya: a critical ethnographic media portrait study - Merry Fridha Tripalupi; Hajidah Fildzah Nadhilah Kusnadi; Rahmat Edi Irawan (Jurnal Studi Komunikasi, 2024)
The current scenario in the public sphere sees women's presence, yet certain professions, including journalism, remain primarily dominated by men. This gender disparity not only affects media policies but also perpetuates stereotypes hindering women's advancement in the industry, thus becoming a subject of interest for the researchers focusing on Surabaya's media landscape. This study aims to analyse the portrait of women in the media by focusing on female journalists in Surabaya, Indonesia. This research used critical ethnography and standpoint theory as a foundation for analysing the phenomenon. Based on the results of the researcher's search, the number of female journalists in Surabaya is at most 30% compared to male journalists. This research uses critical ethnography and standpoint theory, which are used as a foundation to analyse the phenomenon. Based on the results of the researcher's search, the number of female journalists in Surabaya is at most 30% compared to male journalists. The results of this study show clearly that society's norms and stereotypes about gender that do not prioritise female journalists are the cause of discrimination. In fact, this discrimination often occurs unintentionally due to factors in the organisational structure and environment that do not support the inclusion of women. This leads to poor representation of women in the media until there is an endless cycle of the system.